Fabrication of sustainable green bricks by the effective utilization of tannery sludge as main additive. (February 2023) - Jothilingam, M.; Preethi, V.; Sri Chandana, P.; Janardhanan, G.
Abstract: The existing practice of manufacturing construction bricks consumes the maximum amount of natural resources leading to their depletion and severe environmental degradation. The utilization of industrial waste materials is a plausible alternative and is the vision of the Indian government under the waste-to-wealth concept. In the present work, industrial byproducts such as tannery sludge, fly ash, Ground Granulated Blast Furnace Slag (GGBS), and lime were used to develop sustainable green bricks (SGBs) without the need for burning. In the fabrication of SGBs, a combination of lime, fly ash and GGBS was used as binder material. Tannery sludge was replaced up to 30 % in the binder mix, and the optimized mix was used to prepare mortar, followed by solidification and stabilization. Finally, SGBs were water cured with and without prior carbonation. The characteristics of bricks such as microstructure, dry weight, compressive strength, and durability properties like sorptivity, leachability, water absorption and efflorescence were studied. They were comparable to conventional first-class bricks as per the Indian Standards. The compressive strength of the SGBs containing 20 % tannery sludge and 80 % of binder mix (containing 20 % GGBS, 30 % lime and 50 % fly ash) cured with and without carbonation was found to be 8.81 N/mm 2 and 7.62 N/mm 2 ; which is 2.5 and 2.17 times respectively, more than conventional first-class bricks (3.50 N/mm 2 ). The elastic modulus of the carbonated specimen was 3.3 times higher than the non-carbonated mortar specimen, as determined by stress–strain analysis. The increase in the compressive strength was evidenced by the results of various techniques such as Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), Mercury Intrusion Porosimetry (MIP), Energy Dispersive Spectroscopy (EDS), and Thermogravimetric Analysis (TGA). Our results demonstrate that sustainable green bricks could serve as a better replacement for clay bricks and emerge as a carbon-negative material.